Transfer of the Namibian Argistes africanus Simon, 1910 (Araneae: Liocranidae) to Afroceto Lyle & Haddad, 2010 (Trachelidae), with a new synonym - Haddad, Charles R. (Zootaxa, 2019)
Only a single species of the trachelid spider genus Afroceto Lyle & Haddad, 2010 has been recorded from Namibia to date, A. arca Lyle & Haddad, 2010. Examination of the holotype of Argistes africanus Simon, 1910 (Liocranidae), a subadult female specimen, indicates that the species is misplaced and is hereby transferred to Afroceto as A. africana (Simon, 1910) comb. nov. Comparison of the holotype with material of Afroceto arca indicates that this latter species is a junior synonym of A. africana. New records of A. africana from South Africa and Namibia are provided, together with an updated distribution map.